The Temperature and Time Influence of Immersion in Water Solvent against Formaldehyde Salted Level Belanak Fish (Mugil cephalus) - Farid, Mohammad; Jannah, Akyunul; Maunatin, Anik (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2015)
The salted fish is one that is frequently consumed foods by the general public, but people do not realize that a lot of salted fish in the market that contained formaldehyde that can endanger the health of the body and is a food that is not suitable for consumption. The purpose of this study was to determine the temperature and the time required for formaldehyde in salted fish can be reduced. The formaldehyde method used to reduce level in foods, especially salted fish is by using immersion in water. Soaking dried fish is done by using variations in temperature and immersion time. Stage of the study was initiated with the addition of making salted fish with formalin at a concentration of 4%. The fish used is fresh mullet. Variations in temperature used is 40°C, 50°C, 60°C, and 70°C while the variation of time used is 10, 15, 20 and 25 minutes. The level of formaldehyde was analyzed by acid kromatofat and UV-Vis. The analysis results of formaldehyde levels using UV-Vis is the best temperature to reduce levels of formaldehyde in salted fish is 70 ° C by 80.2% and the best time to reduce levels of formaldehyde that is 25 min for 95.6%. Test statistics using Minitab ANOVA variance variant which shows that the influence of the decreased levels of formaldehyde salted fish and produce temperature and the best time is at a temperature of 70 °C and 25 minutes at a time. Keywords: Mugil chepalus, formaldehyde, salted fish, water solvent